2021
DOI: 10.3389/frsc.2021.755313
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Urban Green Spaces: Convergences and Divergences

Abstract: In the context of rapid climate change, it is important to understand public perceptions of urban green spaces (UGSs), because green spaces have enormous potential as instruments for climate change adaptation and mitigation, and because the development of such spaces both requires and benefits from public support. This article attempts, through an extensive literature review, to understand convergences and divergences in perceptions of urban green spaces (UGSs) of city dwellers around the world and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Malik (2017) reported that participatory green space management policy in municipalities was beneficial to green space improvement. Atiqul Haq et al (2021) concluded that it was necessary to adopt an integrated approach to green space design, maintenance, monitoring, and evaluation in order to maximize green space benefits according to the environment and environmental sustainability. Out of all green space improvement variables, participatory management had the greatest effect on green space design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malik (2017) reported that participatory green space management policy in municipalities was beneficial to green space improvement. Atiqul Haq et al (2021) concluded that it was necessary to adopt an integrated approach to green space design, maintenance, monitoring, and evaluation in order to maximize green space benefits according to the environment and environmental sustainability. Out of all green space improvement variables, participatory management had the greatest effect on green space design.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their lower profitability, urban green spaces bring aesthetic, environmental, recreational, social, and health benefits to people (Kruize et al, 2019). Responses to the needs of urban residents and green space visitors are affected by urban planning and management models (Atiqul Haq et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is quite understandable given the increased crime rates that the city of Dar Es Salaam has faced over the past years. In addition, safety is seen as a vital qualitative trait of GSs by [194][195][196] implying that it should be taken into consideration when planning the establishment of open spaces. The feeling of safety could be secured by incorporating security measures such as regular presence of guards or surveillance by digital means [197].…”
Section: Discussionmentioning
confidence: 99%
“…Urban green spaces are an essential component of urban ecosystems. Urban green spaces not only offer aesthetic and comfortable recreational facilities but also render multifaceted ecological functions such as climate regulation, air purification, soil conservation, and enhancement of biodiversity [1][2][3][4]. Accurate assessment and prediction of the environmental conditions for plant growth in green spaces is crucial for ensuring their health and sustainability.…”
Section: Introductionmentioning
confidence: 99%